PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 7 KUPANG - Momang, Maria A; Pamungkas, Bella Theo Tomi; Sunimbar, Sunimbar (Jurnal Geografi, 2023)
The aims of this research are, (1) to determine the effect of the Problem Based Learning learning model on students' critical thinking abilities in geography subjects (2) To determine the increase in students' critical thinking abilities. The type of research used is experimental research. The data collection techniques used in this research are: observation, exams/tests and documentation. The results of this research show that (1) There is an influence of the use of the Problem Based Learning learning model which can be proven from the results of the Independent Sample T-test data analysis using SPSS, namely that the sig. (2-tailed) 0.001<0.05 thus H0 is rejected then Ha is accepted. (2) There is an increase in students' critical thinking skills as seen from the magnitude of changes between the pre-test and post-test. The average N-Gain score obtained by the experimental class was higher, namely 0.52, while the N-Gain score obtained by the control class was 0.44.